Good neighbourhood as an EU accession criterion for Ukraine, Moldova and Georgia? - Christina Eva Griessler (Međunarodni Problemi, 2023)
For the new and future EU candidate countries of Ukraine, Moldova and Georgia, the path to EU membership is based on the same \"established criteria and conditions\" as for the long-term candidates of the Western Balkans (WB). However, the WB’s EU accession process brought with it additional conditions, such as regional cooperation, reconciliation and good neighbourly relations. The EU’s objective at the time was to encourage the countries in the region to improve relations with their neighbours and to deal with the war legacies through regional cooperation initiatives. This raises the question of how, and to what extent, these additional criteria could become part of the EU integration process of Ukraine, Moldova and Georgia – all countries in conflict with neighbouring Russia. The theoretical background of the analysis is the EU’s actorness and its policy of external governance, expanding its normative sphere of influence to non-EU members. The paper discusses the additional WB conditions and identifies similar preconditions in the relevant EU agreements and documents for Ukraine, Moldova and Georgia since 2014. It shows that some of the WB preconditions are used in Eastern European Partner (EaP) countries but are, for now, seemingly less of a priority.